2018
DOI: 10.1038/s41467-018-03482-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis for categorical boundaries in the primate pre-SMA during relative categorization of time intervals

Abstract: Perceptual categorization depends on the assignment of different stimuli to specific groups based, in principle, on the notion of flexible categorical boundaries. To determine the neural basis of categorical boundaries, we record the activity of pre-SMA neurons of monkeys executing an interval categorization task in which the limit between short and long categories changes between blocks of trials within a session. A large population of cells encodes this boundary by reaching a constant peak of activity close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 73 publications
3
63
0
Order By: Relevance
“…Thus, both stimulation and recording results (Romo and Schultz, 1987;Kurata and Wise, 1988;Thaler et al, 1988;Picard and Strick, 2003;Hayduk-Costa et al, 2013;Carlsen et al, 2015;Lara et al, 2018b) argue that SMA contributes to initiation across a broad range of situations. However, the context independence of stimulation effects might appear to conflict with the well-established dependence of SMA neural responses on contextual factors (Tanji and Shima, 1994;Nakamura et al, 1998;Merchant and Georgopoulos, 2006;Merchant et al, 2011Merchant et al, , 2013Nakajima et al, 2013;Merchant and Averbeck, 2017;Lara et al, 2018b;Mendoza et al, 2018;Wang et al, 2018). Indeed, we have confirmed strongly context-dependent responses in SMA (but not motor cortex) in this very same task, at recording sites interspersed among the stimulation sites (Lara et al, 2018b).…”
Section: Context-independent Stimulation Effects Versus Context-depenmentioning
confidence: 45%
See 1 more Smart Citation
“…Thus, both stimulation and recording results (Romo and Schultz, 1987;Kurata and Wise, 1988;Thaler et al, 1988;Picard and Strick, 2003;Hayduk-Costa et al, 2013;Carlsen et al, 2015;Lara et al, 2018b) argue that SMA contributes to initiation across a broad range of situations. However, the context independence of stimulation effects might appear to conflict with the well-established dependence of SMA neural responses on contextual factors (Tanji and Shima, 1994;Nakamura et al, 1998;Merchant and Georgopoulos, 2006;Merchant et al, 2011Merchant et al, , 2013Nakajima et al, 2013;Merchant and Averbeck, 2017;Lara et al, 2018b;Mendoza et al, 2018;Wang et al, 2018). Indeed, we have confirmed strongly context-dependent responses in SMA (but not motor cortex) in this very same task, at recording sites interspersed among the stimulation sites (Lara et al, 2018b).…”
Section: Context-independent Stimulation Effects Versus Context-depenmentioning
confidence: 45%
“…Stimulation may disrupt motor preparation, as occurs in premotor cortex (Churchland and Shenoy, 2007). Stimulation may alter computations related to interval timing (Mita et al, 2009;Merchant et al, 2013;Merchant and de Lafuente, 2014;Cadena-Valencia et al, 2018) or time discrimination (Mendoza et al, 2018). Producing appropriately timed movements, in different ways for the different contexts, is a key aspect of our task.…”
Section: Nature Of Computation Being Disruptedmentioning
confidence: 99%
“…With respect to the potential neural mediators of the effects in our study, we note that recent evidence suggests that neurons within the supplementary motor area (SMA) code for subjective duration (Mita et al, 2009), and EEG activity putatively driven by the SMA has been shown to vary on a trial-by-trial basis with duration categorization (Wiener and Thompson, 2015). Further evidence has recently revealed that SMA neurons encode a categorical boundary for classifying intervals (Mendoza et al, 2018). Yet, alternative explanations suggest this region more broadly encodes response caution, and the evaluation of evidence in favor of a decision (van et al, 2011).…”
Section: Discussionmentioning
confidence: 56%
“…One possibility here is that frontal beta oscillations underlie proximity to a memory standard used for judging relative duration (Wiener, et al 2018;Mendoza, et al 2018), whereas posterior alpha oscillations underlie the encoding of spatial distances in memory (Khader, et al 2010;Sauseng, et al 2005;Sutterer, et al 2019). Notably, in an fMRI version of the distance reproduction task used here, greater hippocampal activation was observed as subjects completed distance reproductions, which further correlated with the degree of central tendency between subjects (Wiener, et al 2016).…”
Section: Discussionmentioning
confidence: 82%